Historical catastrophes: hurricanes & tornadoes - Cutchen, Billye W., 1930-; Brown, Walter R., 1929-; Brown, Walter R., 1929- ([Reading, Mass.] Addison-Wesley, 1972)
Describes the damage done by several major hurricanes and tornadoes since the beginning of the twentieth century. Also discusses the role of the Weather Service in discovering storms and alerting people of impending danger.
"An Addisonian Press book."
13 31
Keywords: Hurricanes -- Juvenile literature; Tornadoes -- Juvenile literature; Hurricanes; Tornadoes